First record of the Harpy Eagle Harpia harpyja in the Pantanal, with data about breeding activity - Ubaid, Flavio Kulaif [UNESP]; Ferreira, Luciana Pinheiro; Oliveira Junior, Samuel Borges de; Zuquim Antas, Paulo de Tarso (Soc Brasileira Ornitologia, 2011)
First record of the Harpy Eagle Harpia harpyja in the Pantanal, with data about breeding activity. The first reliable encounter of the Harpy Eagle Harpia harpyja in the Pantanal floodplains is reported, with information on its breeding activity in the region, as well as some prey. A nest was found in August 2009, located in Barao de Melgaco County, northern portion of the Pantanal, with a 60-90-day-old eaglet. After a windy storm on August 30, the nest fell, causing the death of the nestling. In March 2010 another nest was located about 2.6 km distant from the first. We emphasize the importance of this record, and the need for a monitoring program to evaluate the true status of the Harpy Eagle in the northern portion of the Pantanal and nearby areas.
Keywords: Harpy Eagle; Accipitriformes; Accipitridae; Mato Grosso